THE ASSOCIATION OF THE SEXUAL PRACTICE WITH PROTECTIVE METHODS AND SELFEFFICACY OF THE STUDENTS OF VLORA UNIVERSITY TO HIV INFECTION - Lalo, Rezarta; Theodhosi, Gjergji; Kamberi, Fatjona (European Scientific Journal, ESJ, 2015)
Introduction: Regardless the fact of whether a country has a low or a high prevalence rate of AIDS, reducing the vulnerability of young people to HIV infection is the principal defense against the epidemics of the future. Purpose: To establish the association of the sexual practice with knowledges about prevention measures and self-efficacy of the students of Vlora University to HIV infection. Methodology: This is a descriptive study where quantitative method was used for the data and information resulting from a survey structured in the form of a questionnaire. The study participants were 721 randomly selected students from the Vlora University. For statistical analysis of the data was used statistical program SAS version 9.1. Results: The average age of the students was 20.75 ± 2.2 years, 56.45% were female and 43.55% male. 29% of the students manifest risky sexual practices and 71% safe practices. In total we notices that 46.66% of the students did not have good knowledge on preventive measures to HIV/AIDS. The Chi-square=0.3113>0.05 indicator does not show statistical significance between students’sexual practices and knowledge of preventive measures. In the students with safe practices 58% of them have very good and good knowledge, the ones with risky sexual practices only 55% have very good and good knowledge Conclusions: The students of Vlora University do not have the sufficient knowledge on the preventive measures. HIV/AIDS-related education programs should include specific interventions to change practices, along with preventive measures knowledge